Challenges to Measure and Compare Disability: A Methodological Concern - Subedi, Madhusudan (Dhaulagiri Journal of Sociology and Anthropology, 2013)
Disability is a complex multidimensional condition and poses a number of challenges for measurement. Operational measures of disability vary according to the purpose and application of the data and the aspects of disability examined. Various sources can be used to examine the prevalence of disability, but they are not directly comparable because they use different approaches to estimating and measuring disability. The definitional issues underlie some of the difficulties in statistical analysis, and to understand the conceptual questions shaping the efforts of those working in the various fields relating to disability. Disability data of Nepal is no exception, and researchers and organizations that have been working for people with disabilities have questioned the reliability of such data. DOI: http://dx.doi.org/10.3126/dsaj.v6i0.8476 Dhaulagiri Journal of Sociology and Anthropology Vol. 6, 2012 1-24